Associations of accelerometer-based sleep duration and self-reported sleep difficulties with cognitive function in late mid-life: The Finnish Retirement and Aging Study - Teräs, Tea (My University, 2019)
With the population aging, prevalence of cognitive deficits is increasing. To suppress this increase it is crucial to detect underlying risk factors behind cognitive deficits and enable primary prevention early enough in the life-course. Previous studies have suggested that sleep duration and sleep difficulties are associated with cognition in old age, but little is known of this association in the late mid-life. The aim of this study is to examine the associations of accelerometer-based sleep duration and self-reported sleep difficulties with different domains of cognition among aging workers. The study population (N=289) consists of participants of the Finnish Retirement and Aging Study (FIREA). Sleep duration was measured with wrist-worn accelerometers, and the participants were divided into short (<7h/night), mid-range (7-9h/night) and long sleepers (≥9h/night). Sleep difficulties were evaluated with Jenkin’s Sleep Problem Scale (difficulties falling asleep, difficulties maintaining sleep, waking up too early in the morning, and nonrestorative sleep). The participants also underwent comprehensive cognitive testing including computer-based cognitive tests. The cognitive tests were grouped to cover three cognitive domains: 1) memory, 2) executive function, and 3) attention and information processing. Greater difficulties in waking up too early in the morning and nonrestorative sleep were associated with poorer executive function. Compared to mid-range and short sleepers, long sleepers tended to have poorer cognitive function, but the associations were not statistically significant. These results suggest that sleep difficulties are associated with poorer cognitive function, and therefore promoting better sleep quality may translate into better cognitive health in late mid-life.
Keywords: unenpituus, unenlaatu, univaikeudet, kognitio